2011
DOI: 10.1007/s00266-011-9844-3
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Prospective Study of TissuGlu® Surgical Adhesive in the Management of Wound Drainage Following Abdominoplasty

Abstract: The application of TissuGlu in abdominoplasty is safe and may decrease wound drainage and the length of time required for postsurgical drains in abdominoplasty patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 28 publications
1
56
0
1
Order By: Relevance
“…In addition, this tissue adhesive had higher healing power compared to suture, fibrin glue and cyanoacrylate after applying on the skin incision of rats [55]. The use of surgical adhesives for controlling wound drainage and seroma formation has been also studied [111]. For example, Walgenbach et al .…”
Section: Applications Of Elastic Surgical Sealantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this tissue adhesive had higher healing power compared to suture, fibrin glue and cyanoacrylate after applying on the skin incision of rats [55]. The use of surgical adhesives for controlling wound drainage and seroma formation has been also studied [111]. For example, Walgenbach et al .…”
Section: Applications Of Elastic Surgical Sealantsmentioning
confidence: 99%
“…used a lysine-based urethane adhesive TissuGlue to control drain time and volume in patients underwent abdominoplasty. It was found that TissueGlue significantly decreased the wound drainage and time required for postsurgical drains following abdominoplasty [111]. In a recent study, injectable citrate-based mussel-inspired tissue adhesives (iCMBAs) with high adhesion strength to wet surfaces were developed as sutureless wound closure bioadhesives (Figure 6b) [112].…”
Section: Applications Of Elastic Surgical Sealantsmentioning
confidence: 99%
“…Il apparaît en fait que les séromes sont au mieux remplacés par des lymphorrhées (OR = 4,7), que l'utilisation des lames ne diminue pas le taux d'hématomes et que le taux de troubles de la cicatrisation et le taux global de complications sont significativement plus importants en cas d'utilisation de lames (OR = 5,5). Plusieurs stratégies ont été décrites afin de diminuer la survenue de séromes ; certains prônent le capitonnage seul, d'autres l'associent à un drainage par drains de Redons, ou encore l'emploi de colle de fibrine[17][18][19] Les conclusions de ces travaux sont contradictoires, pour nous, l'association capitonnage et drainage semble être une bonne option[20].Le taux d'infections est aussi plus important mais de manière non significative (15 % contre 8,4 %). Même si nous n'avons pas retrouvé de fasciite nécrosante dans notre série, cette complication dramatique semble être encore plus crainte chez l'ancien obèse[21].Limites de l'étudeNotre étude présente quelques biais et limites : il s'agit d'une revue de dossiers, les patients n'ont pas été reconvoqués et quelques données ont pu être mal renseignées.…”
unclassified
“…Materials used in surgical glues, such as fibrin glue, albumin and urethane, can rapidly form a rigid, hardened structure and also demonstrate good biocompatibility [187189]. Among the available options, fibrin glue has been widely investigated as a carrier for drugs, biological factors, or genes [190194].…”
Section: Drug Delivery Medical Devices For Soft Tissue Repairmentioning
confidence: 99%